A current insight into Human Knee Menisci - Maciej Pasiński; Maria Zabrzyńska; Michalina Adamczyk; Maciej Sokołowski; Tadeusz Głos; Martyna Ziejka; Piotr Augustynowicz; Kamil Boguszewski; Wojciech Piotrowski; Błachowski Michał; Joanna Górska; Jan Zabrzyński (Translational Research in Anatomy, 2023)
Menisci of the knee are semilunar-shaped structures located between the condyles of the femur and tibia, together with articular surfaces of the tibial condyles form the acetabulum of the knee joint. They have multiple functions, affecting the proper joint biomechanics, even though in the past they were perceived as embryonic remnants. Menisci are involved in such vital functions as: load bearing, joint stability, joint congruity, increasing joint contact area, decreasing joint contact stresses, protection of articular cartilage, shock absorption, lubrication, limitation of extreme movement and proprioception.Menisci arise from a condensation of the intermediate layer of mesenchymal tissue. At later stages of development, it is observed a gradual decrease in the cellularity of the structure and increase of the collagen fibers, where collagen type I is a major fibrillar component. The meniscus is composed of an extracellular matrix mainly filled with water (72%) and collagen (22%), with a minority of proteoglycans, glycoproteins, peptides, and local cells - fibrochondrocytes.When it comes to vascularization, two main areas are present in the structure of meniscus: red-red zone - vascular, white-white zone – rather avascular, and in between the red-white zone. Major vascularization is ensured by the popliteal artery branches: medial, lateral and middle geniculate arteries. It was shown that meniscus can be vascularized in each zone, what is linked with the hypovascular zone regenerative potential. The vascularization pattern and nutritional status of a torn meniscus and the morphological pattern of the tear are crucial factors determining the success of a meniscus surgery. The healing potential of a torn meniscus is directly dependent on its blood supply.At present, it is known that proper performance of the knee joint is directly proportional to the amount of meniscus tissue. Their involvement in the multiple important functions leads to modern solutions focused on saving meniscus tissue.